BREAKFAST BY JOHN STEINBECK: A SITE FOR IDEOLOGICAL INTERPELLATIONS - Saleem, Muhammad (European Scientific Journal, ESJ, 2013)
This study investigates Breakfast, a short fiction by John Steinbeck, in the light of Louis Althusser’s theory of ideology expounded in his essay Ideological State Apparatuses (ISAs). According to this post-Marxist philosopher, social institutions like church, family, education, and morality paradigm are political agencies that work to inculcate the spirit of allegiance to the existing ideologies among the individuals of a given social formation. Interpellation is an essentially significant mode that is consistently employed to bend the living individuals as ‘subjects’ to the dominant institutional ideologies. The interpellated subjects, the subjected souls, are addressed in such a way that they continue to believe themselves as contented, autonomous and independent entities. But there are some occasions when the readers encounter the irregularities and fault-lines in the ideologically woven smooth literary text. This dialogic aspect of the text is central to its political character. This study would use the popped up chunks of the given discourse to analyse how the ideological processes keep the addressed characters in a state of complacency. It is hoped that this paper would enable the readers to confront the strategic workings of the ideological hailings; they are also expected to spot the contradictions in the politically maneuvered text. These infrequent but subtle hints serve as a type of protest, resistance and critical deixis to the aestheticised ideological hegemonies.